2018
DOI: 10.1038/s41598-018-30759-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mosaic chromosome Y loss and associations with mortality in the UK Biobank

Abstract: Mosaic loss of the Y chromosome (mLOY) is the most commonly reported large structural somatic event. Previous studies have indicated age and cigarette smoking increase the risk of mLOY, but the relationship of other exposures with mLOY and mLOY with disease has not been adequately investigated. We characterized mLOY in a large cohort of 223,338 men from the UK Biobank by scanning for deviations in genotyping array median log2 intensity ratios (mLRR) of the Y chromosome using a standard algorithm. A total of 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
156
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(163 citation statements)
references
References 30 publications
5
156
1
1
Order By: Relevance
“…Additionally, the LOY-associated genes encoding cyclins and cyclindependent kinases, CCND3, CDKN1B and CDKN1C, are also implicated in pancreatic β-cell growth and maturation. We hypothesise that the previously reported association between clonal mosaicism in blood and T2D 15,46 may reflect a common susceptibility to cell cycle dysregulation and genome instability, which lead to both increased clonal mosaicism and reduced pancreatic β -cell mass.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Additionally, the LOY-associated genes encoding cyclins and cyclindependent kinases, CCND3, CDKN1B and CDKN1C, are also implicated in pancreatic β-cell growth and maturation. We hypothesise that the previously reported association between clonal mosaicism in blood and T2D 15,46 may reflect a common susceptibility to cell cycle dysregulation and genome instability, which lead to both increased clonal mosaicism and reduced pancreatic β -cell mass.…”
Section: Discussionmentioning
confidence: 89%
“…We developed a new statistical approach for identifying male individuals with LOY based on allelespecific genotyping intensities in the pseudoautosomal region (PAR) of the sex chromosomes. In contrast to previous work that has quantified Y chromosome loss based on median genotyping intensity over the non-pseudoautosomal region of the Y chromosome (mLRR-Y) [12][13][14][15] , our approach leverages the diploid nature of the PAR to ascertain mosaic Y loss based on differences between maternal (X PAR) vs. paternal (Y PAR) allelic intensities at heterozygous sites: mosaic Y loss causes Y PAR intensities to decrease relative to X PAR intensities. This intuition can be harnessed even in population cohorts in which absolute phase information (i.e., information about maternal vs. paternal inheritance of alleles) is unavailable: we can overcome this obstacle by performing statistical phasing and subsequently identifying evidence of an imbalance in allelic intensities between the two statistically phased haplotypes (accounting for the possibility of phase switch errors) 5,6 .…”
Section: Phenotype Preparation In Uk Biobankmentioning
confidence: 99%
See 1 more Smart Citation
“…We provide the first mechanistic explanation for the associations between LOY in blood and risk for disease in other organs.Recent epidemiological analyses have challenged the view that LOY in blood cells is phenotypically neutral. Studies have identified increased risks for men with LOY in connection with all-cause mortality [8,9], Alzheimer's disease [10], various forms of cancer [8,[11][12][13], autoimmune conditions [14,15], age-related macular degeneration [16], cardiovascular disease [17], type 2 diabetes and obesity [9]. Furthermore, it has been known for centuries that males have a shorter life expectancy [18][19][20].…”
mentioning
confidence: 99%
“…The most common somatic mutation in humans is the mosaic loss of chromosome Y (mLOY) in men. Recent evidence suggests the important role of mLOY in numerous diseases, being a biological factor that contributes to overall male mortality (1,2) and, therefore, is likely to play an important role in male-specific treatments of disease. In particular, mLOY in blood cells increases with age, and is associated with smoking and with the risk of several age-related disorders, including hematological and non-hematological cancers, macular degeneration (3), Alzheimer's disease (4), major cardiovascular events (5) and suicidal behaviors (6).…”
Section: Introductionmentioning
confidence: 99%